Guyana : the growth of a nation 1966 - 2016 - the official golden jubilee of Independence bookazine (Corbin Media Group EcclesGY, 2016)
Presents photographic memories from each decade and includes maps, articles on the arts, entertainment, trivia
Keywords: GUYANA